2018
DOI: 10.1177/1534734618785844
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Spectral Analysis Accurately Identifies the Bacterial Signature in Infected Chronic Foot Ulcers in People With Diabetes

Abstract: Diabetic foot infections are a major cause of hospitalization, and delayed treatment can lead to numerous complications. The aim of this research was to investigate high-resolution spectroscopy of the wound center and periwound area for real-time estimation of multispectral signature of bacteria at the base of diabetic foot ulcers. We investigated the spectrum of the reflected visual light from diabetic foot ulcers and developed a method that identifies the presence of bacteria in the wound infections. We unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…In most cases (n = 19) the multi‐patient studies were reported 1,2,5,7,54‐68 . However, in some cases (n = 12), the case studies were reported 8,50,69‐78 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In most cases (n = 19) the multi‐patient studies were reported 1,2,5,7,54‐68 . However, in some cases (n = 12), the case studies were reported 8,50,69‐78 …”
Section: Resultsmentioning
confidence: 99%
“…In several studies, spectroscopic systems were used at a single 64,65 location to detect spatial heterogeneity of the blood flow. A spectroscopic system was used by Poosapadi et al 68 to discriminate between Staphylococcus aureus and Escherichia coli .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations